Gamification of Pancasila Education: The Effect of HAKI Literacy Snakes and Ladders Media on Elementary School Learning Outcomes - Fahma Aulia Rodhifah; Muh Muhaimin (Universitas Pendidikan Ganesha, 2025)
The purpose of this study was to determine whether and how the Interactive Literacy Resource (IPR) Snakes and Ladders influenced fourth grade students' performance in Pancasila subject, focusing on the Rights and Duties unit. Traditional teaching methods and lack of engaging educational media have long been blamed for students' poor performance in class. Using a pre-test, post-test, and control group design model, this survey served as a quasi-experimental study. The 38 students who participated in this study were divided into two groups. One group used the Snakes and Ladders Literacy Game Media as an experimental tool, while the other group continued to use more conventional teaching methods. Learning outcome tests, observation sheets and interview guides were some of the instruments used in this study. The results showed that the experimental group achieved significantly better learning outcomes compared to the control group. Compared to the control group's average post-test score of 71.95, the experimental group's was 88.53. The significant difference in learning outcomes between the two groups was shown by the significance value of the independent sample t-test of 0.000 <0.05. In addition, the N-Gain score was significantly higher in the experimental group (70.58%) than the control group (24.48%). Taking all factors into consideration, these findings prove that the educational game Snakes and Ladders is of great interest to students and helps them learn in a fun and interesting way. Therefore, we propose this learning tool as a substitute for teaching Pancasila in primary schools.